Problems of Law Enforcement Regarding Criminal Acts of Abuse of Dangerous Food Production - Suleman, Suaib R; Puluhulawa, Moh. R. U; Achir, Nuvazria (Estudiante Law Journal, 2024)
This research aims to determine the factors that hinder law enforcement against criminal acts of misuse of dangerous food production in Gorontalo Province. The type of research used is empirical legal research with a qualitative approach. The results of this research show that the problems of law enforcement regarding criminal acts of misuse of dangerous food production in Gorontalo Province include: first, internal factors caused by facilities and facilities, the personality and mentality of personnel, the quality of operational funding personnel, and the difficulty of uncovering evidence. Second, external factors caused by leaking information about raids to perpetrators, lack of awareness in fulfilling their rights and responsibilities as business actors, limited employment opportunities, lack of community participation, and public legal awareness